2013
DOI: 10.4018/jvcsn.2013010101
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Customer Relationship Management-Co-Creation and Collaboration through Online Communities

Abstract: There are four trends reshaping the world of business-technological advances and the speed with which new technologies are created and copied, the loss of geographic advantage resulting from globalization, the shake-up of traditionally stable industries as a result of deregulation and the rising power of the consumer and their ability to get what they want, when they want it, from whomever they want. With this in mind, the collaboration experience becomes one of the greatest competitive aspects for a business’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…2.1 Professional Virtual Communities (VCoP) Alavi (2013), defines the VCoP as "social network of individuals, who interact through social media, potentially crossing geographical, political and psychological boundaries in order to pursue mutual interest or goals". It has been observed that employees in a VCoP collectively learn to achieve their knowledge seeking objectives (Frank et al 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…2.1 Professional Virtual Communities (VCoP) Alavi (2013), defines the VCoP as "social network of individuals, who interact through social media, potentially crossing geographical, political and psychological boundaries in order to pursue mutual interest or goals". It has been observed that employees in a VCoP collectively learn to achieve their knowledge seeking objectives (Frank et al 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%